The criminal policy of the state in the formation of the criminal pro-ceedings measures of protection of rights and interests of citizens - I. N. Kondrat (Vestnik MGIMO-Universiteta, 2012)
The author examines the influence of criminal policy on the formation of criminal proceedings measures of protection or rights and interests of citizens in the fight against crime. The leading role of criminal policy in the formation and imple-menting of the criminal proceedings policy is shown in the article. On the basis of the juridical content of the lawful politics the author is coming to the conclusion that one can judge about the content of the criminal proceedings policy of the state using the legislatively formulated principles of criminal proceedings. Such policy shows the attitude of the state power to the fight against criminal violations of the interests of individual, society and state, to the proceedings methods and measures of such fight and also to the guarantees against unfounded prosecution and conviction of citizens. First of all the implementation of the criminal proceedings policy depends on the level of the lawful awareness of the law enforcement recipients.